Pengenalan Pencatatan Akuntansi Sederhana Usaha Dagang Koliwolon - Kuki, Emerensiana Katharina; Korina, Theovila; Desita, Fransiska Natalia; Diaz, Yohana Wanti (INCOME: Indonesian Journal of Community Service and Engagement, 2023)
Very fast and dynamic business developments and the increasing level of business competition between competitors require Micro, Small and Medium Enterprises (MSME) players to move quickly to keep up with the times. Apart from marketing, MSME players also need to prepare as best as possible the management of the 'home' industry for the survival of a business, including readiness for business management, business financial management, stock management of goods up to consumer service management. Of course, these preparations cannot be done alone, especially not all MSMEs understand the whole problem, so MSME actors need to be assisted and accompanied. Community service program held at the Koliwolo trading business with the aim of finding out expenses and income in the Koliwolon Trading Business. This introduction to Simple Accounting is expected to support the Koliwolon trading business to find out income and expenses. The method used in this PKM is skills training regarding the introduction of simple accounting records. The result obtained from this activity is that the introduction of simple accounting records for the koliwolon trading business can be well received and applied to trading businesses.